2015
DOI: 10.1073/pnas.1511477112
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms tracking popularity in real-world social networks

Abstract: Differences in popularity are a key aspect of status in virtually all human groups and shape social interactions within them. Little is known, however, about how we track and neurally represent others' popularity. We addressed this question in two real-world social networks using sociometric methods to quantify popularity. Each group member (perceiver) viewed faces of every other group member (target) while whole-brain functional MRI data were collected. Independent functional localizer tasks were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 60 publications
(112 reference statements)
5
102
1
Order By: Relevance
“…http://dx.doi.org/10.1101/098988 doi: bioRxiv preprint first posted online Jan. 9, 2017; encode extraversion 22 , which is modestly correlated with EC 25 , suggesting that this region may encode dispositional tendencies common to both extraversion and EC. In addition, recent work has also shown that the medial parietal cortex, as well as other regions involved in inferring others' mental states, intentions, and traits (e.g., MPFC; temporoparietal junction), responds preferentially to well-liked individuals, which is thought to reflect perceivers being preferentially motivated to understand the internal states of popular others 26 . The current findings are consistent with the notion that brain regions that represent others' internal states and behavioral tendencies (e.g., PCC, MPFC) track sociometric status, and suggest that like other facets of social status (e.g., dominance 27 , prestige 28 ), EC may modulate attention to the internal states of others.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…http://dx.doi.org/10.1101/098988 doi: bioRxiv preprint first posted online Jan. 9, 2017; encode extraversion 22 , which is modestly correlated with EC 25 , suggesting that this region may encode dispositional tendencies common to both extraversion and EC. In addition, recent work has also shown that the medial parietal cortex, as well as other regions involved in inferring others' mental states, intentions, and traits (e.g., MPFC; temporoparietal junction), responds preferentially to well-liked individuals, which is thought to reflect perceivers being preferentially motivated to understand the internal states of popular others 26 . The current findings are consistent with the notion that brain regions that represent others' internal states and behavioral tendencies (e.g., PCC, MPFC) track sociometric status, and suggest that like other facets of social status (e.g., dominance 27 , prestige 28 ), EC may modulate attention to the internal states of others.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…It joins a burgeoning literature (Carley 1989;DiMaggio 1997;Morgan and Schwalbe 1990;Cerulo 2002;Vaisey 2008Vaisey , 2009Srivastava and Banaji 2011;Brekhus 2015;Zerubavel et al 2015) that underscores the value of drawing on concepts and methods from cognitive and social psychology to address longstanding sociological questions.  "Uhm, I like my eggs scrambled.…”
Section: Resultsmentioning
confidence: 97%
“…It is also possible that other nonverbal cues, which we did not study in our exploratory analysis, are also associated with judgments about others' social worlds. For example, recent developments in cognitive science suggest that observing popular others elicits value signals that facilitate one's understanding of their mental states (Zerubavel et al 2015). Replication of this approach in field settings is necessary to clarify the role of these contextual factors in the accuracy of interpersonal judgments.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…It plays a key role in social communication (O’Donnell et al, 2015; Tang et al, 2016), even in the implicit condition (Zerubavel et al, 2015; Welborn et al, 2016). In the conditions without face-to face communication, activity at TPJ was highly increased when participant engaged in more consideration to other’s perspective (Falk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%